(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: تهدف هذه الدراسة إلى بيان أثر جودة الخدمات التعليمية على رضا الأولياء في المدارس الخاصة بالجزائر، ولتحقيق ذلك صممت الباحثتين إستبانة تضمنت (43) فقرة لجمع المعلومات الأولية من أولياء الأمور. وعلى ضوء ذلك تم استخدام المنهج ا الوصفي ومن ثم جمع البيانات وتحليلها واختبار الفرضيات بواسطة برنامج ـ (Spss.25). بعد عمليات تحليل البيانات واختبار فرضيات الدراسة توصلت الدراسة إلى عدد من النتائج منها: تحسين جودة الخدمة التربوية ينعكس إيجاباً على مستوى رضا الأولياء.كما أوضحت الدراسة أن هناك تأثيراً ذو دلالة إحصائية لجودة الخدمات التعليمية الخاصة على رضا الأولياء بقيمة دلالة (0.05)، كما توجد فروق في رضا أولياء التلاميذ تعزى للمستوى التعليمي لهم والعمر. وخلصت الدراسة إلى مجموعة من التوصيات أهمها: يجب أن تستمر المدارس في التأكيد على الالتزام والتطوير المستمر لجودة الهياكل التعليمية، جودة الإجراءات، جودة التفاعل وجودة النتائج لتحسين البرامج المعتمدة في المدارس الخاصة. كلمات دالة: الخدمات التعليمية، جودة الخدمات التعليمية، المدارس الخاصة، رضا الأولياء، الجزائر. Abstract: This study aims to demonstrate the impact of the quality of educational services on the satisfaction of students’ parents in private schools in Algeria. A questionnaire of (43) items was used to collect primary information. A descriptive analytic method was used, data was collected and analysed, and hypotheses tested using the (Spss.25) program. The study reached a number of results, such as: there is a statistically significant effect of the quality of special educational services on parents’ satisfaction, at significance threshold of (0.05). The results show too that there are also differences in the satisfaction levels of the parents due to their educational level and age. The study concluded the following recommendations: Schools should continue to emphasize the commitment and continuous development of the quality of educational structures, the quality of procedures, the quality of interaction and the quality of results to improve the programs accredited in private schools. Key words: Educational Services, The Quality of Educational Services, Private schools, Parents Satisfaction, Algeria